Explosion of rice flour at different concentration and moisture content - Wan Zaiton, Wan Sulaiman; Mohd Fadzil, Mohd Idris; Jolius, Gimbun; Siti Zubaidah, Sulaiman (IOP Publishing, 2020)
The dust explosion characteristics of commercial rice flour towards different concentration were analysed. Experiments were performed in 20 L spherical explosion chamber to obtain maximum explosion overpressure (Pmax), rate of pressure rise (dP/dT), and minimum explosibility concentration (MEC) of undried and dried commercial rice flour. The dust samples and air mixtures were ignited by two chemical ignitors at ignition time of 100 ms. The Kistler Piezoelectric pressure sensors were used to quantify the propagation of pressure wave during the explosion process. The moisture content of the samples were measured by using proximate analysis. The Pmax was obtained at the highest pressure over the range of concentrations. Pmax for undried rice flour and dried flour are 10.0 bar and 10.4 bar respectively at 1000 kg/m3. Both of the Pmax were attained at the highest level of concentration. The highest value of dP/dT of undried was 70 bar/s at 1000 kg/m3 but for dried rice flour, the highest value obtained was 63.5 bar/s at 750 kg/m3. MEC for both dried and undried was 500 kg/m3. This study concluded that as the concentration increases, the severity of dust explosion would also increase and the presence of moisture decrease the severity of the rice flour explosion but not too significant at ignition time of 100 ms.